Kia Tū Pakari ngā Māhuri: Amplifying the Voices of Rangatahi Māori in the Criminal Justice System and Their Educational Experiences. - Flavell, William (Auckland University of Technology, 2023)
This qualitative, kaupapa Māori research project describes the school experiences of five rangatahi Māori, aged between 18 and 24 years, with experience in the criminal justice system. Due to the Covid-19 restrictions, data were gathered via semi-structured individual video conference interviews. The interviews aimed to explore if there was a connection between the school experiences of the rangatahi Māori and their offending. The narrative interview data were transcribed, coded, and categorised into significant themes related to the research questions using the thematic analysis method. Understanding the school experiences of the rangatahi Māori who were interviewed can be recognised in terms of key factors such as Māori identity, success / accomplishments, connectedness / disconnection, and school disengagement. Some of the findings from this study show that most of the participants academically struggled and had negative schooling experiences, became disengaged from school, had high levels of truancy, and did not fully complete their schooling. The findings of this study contribute to existing academic literature about Māori youth offending and education because the voices of rangatahi Māori have been privileged. This research will also guide whānau, policymakers, schools, and community leaders to better support rangatahi Māori in both the education and the criminal justice systems.